SCANNING ELECTRON MICROSCOPY OF “ROSA” FILTER ELEMENTS FROM HEMOFENIX APPARATUS, AND OF BLOOD IN MEMBRANE PLASMAPHERESIS AND LASER IRRADIATION - I. M. Baybekov; A. K. Butaev; B. A. Saidkhanov (Вестник трансплантологии и искусственных органов)
Aim. To study with scanning electron microscopy an interaction between structural elements of “Rosa” filters (a component of HEMOFENIХ) with erythrocytes during membrane plasmapheresis and under the effect of la- ser irradiation performed during plasmapheresis. Materials and methods. Using scanning electron microscopy and morphometry, blood cells and plasma-filter components were studied in patients with myasthenia gravis. Results. It has been revealed that the percentage of pathologic forms of erythrocytes increased in peripheral blood of patients with myasthenia gravis. Plasmapheresis leads to an increase in the number of pathologic forms of erythrocytes in peripheral blood as well as on plasma-filter components. Conclusion. Laser irradiation, in turn, promotes the significant reduction of pathological forms of erythrocytes number in peripheral blood and on plasma-filter components.